Analyzing pericytes under mild traumatic brain injury using 3D cultures and dielectric elastomer actuators - Wu, Yi-Han; Park, Thomas I-H; Kwon, Eryn; Feng, Sheryl; Schweder, Patrick; Dragunow, Mike; Shim, Vickie; Rosset, Samuel (Frontiers in Neuroscience, 2022)
Traumatic brain injury (TBI) is defined as brain damage due to an external force that negatively impacts brain function. Up to 90% of all TBIs are considered in the mild severity range (mTBI) but there is still no therapeutic solution available. Therefore, further understanding of the mTBI pathology is required. To assist with this understanding, we developed a cell injury device (CID) based on a dielectric elastomer actuator (DEA), which is capable of modelling mTBI via injuring cultured cells with mechanical stretching. Our injury model is the first to use patient-derived brain pericyte cells, which are ubiquitous cells in the brain involved in injury response. Pericytes were cultured in our CIDs and mechanically strained up to 40%, and by at least 20%, prior to gene expression analysis. Our injury model is capable of producing a patient-dependent gene expression changes, at 4 and 48 h, of the genes implicated in pathological changes after TBI. The results of this study demonstrate that our CID is a suitable tool for simulating TBI as an in vitro stretch injury model, that is sensitive enough to induce patient-specific responses to mechanical impacts, the hallmark of mTBI.